The type IA supernova rate in intermediate redshift galaxy clusters - Kasai, Eli Kunwiji (Department of Mathematics and Applied Mathematics, 2014)
Studies of Type Ia supernovae (SNe Ia) in galaxy clusters can tell us about the metal enrichment of the intra-cluster medium, constrain the star formation history of cluster galaxies, aid us in the investigations of the progenitor systems of SNe Ia, act as tracers of the intra-cluster stellar population and can be used in measuring distances over extragalactic scales, which is relevant to supernova cosmology. However, the value of the cluster Type Ia supernova (SN Ia) rate at intermediate redshifts has not been well constrained and this hampers our ability to derive accurately the parameters needed in addressing the topics listed above. We have performed a search for supernovae and other transients in six galaxy clusters, located in the redshift range 0:3 < z < 0:9 to derive the cluster Type Ia supernova (SN Ia) rate.